Lower extremity bypass in patients with diabetic foot ulcers - Gibbons, Gary W (The Surgical clinics of North America, 2003)
The assessment and management of ischemia for the diabetic patient must be a part of an evidence-based treatment algorithm for wound healing. In 1999, the American Diabetes Association published a consensus position to provide guidance to health care professionals who manage foot wounds in patients with diabetes. The consensus panel recognized six approaches that are supported by clinical trials or well-established principles of wound healing: off-loading, debridement, dressings, antibiotics, vascular reconstruction, and amputation or reconstructive foot surgery when necessary. Adjunctive medical therapies include normalization of blood glucose, treatment of comorbid conditions, control of edema, nutritional repletion, and physical and emotional therapy. Education and prevention of recurrence are essential in any treatment algorithm. Box 1 and Box 2 are algorithms developed by the author and used in clinical management of diabetic lower extremity wounds. The author's multidisciplinary team approach is evidenced based with documented healing and a reduction in amputation at every level. For the patient, it best allows a return to function and well-being. Focusing on quality maximizes the cost/benefit ratio.